Comparison of Antibacterial Effects of Photodynamic Therapy, Modified Triple Antibiotic Paste and Calcium Hydroxide on Root Canals Infected With Enterococcus faecalis: An In Vitro Study - Asnaashari, Mohammad (Laser Application in Medical Sciences Research Center, 2019)

(untitled) (J Lasers Med Sci)
Introduction: A pivotal issue to achieve success in the treatment of the root canal is root canal disinfection. One of the most important bacteria that infect the root canal is Enterococcus faecalis. This study seeks to examine the effectiveness of 3 methods for disinfecting the root canal: photodynamic therapy, modified triple antibiotic paste (MTAP), and calcium hydroxide. Methods: Sixty-two single-rooted extracted anterior teeth were collected. After cleaning and disinfecting the teeth, their crowns were cut at the CEJ point. The root canals were shaped to the working length up to file F3 ProTaper (F1, F2, F3). EDTA 17% and sodium hypochlorite 2.5% were used for 5 minutes to wash and remove the smear layer, and then the apical foramen was sealed using composite. After that, the teeth were sterilized in an autoclave at 121°C for 15 minutes. Then 10 samples were taken randomly as the negative control. The remaining samples were immersed and cultivated in a suspension containing E. faecalis for 21 days. Then the samples were divided into 5 groups: 2 positive control groups, 1 group treated with the antibiotic paste with the concentration of 1 mg/mL, 1 group treated with calcium hydroxide, and 1 group treated with photodynamic therapy. Then, to collect the biofilm, the ProTaper file F4 was used. After that, the microbial suspension was provided and counting the colonies was carried out to compare the groups. Results: The findings indicated that the amount of CFU/mg of MTAP samples, including clindamycin, metronidazole, ciprofloxacin in the concentration of 1 mg/mL and photodynamic therapy and calcium hydroxide was lower than that in the control group. Antibiotic paste cleansed the root canal up to 99.9%. Photodynamic therapy reduced the amount of CFU/mg to 98.8%, and calcium hydroxide reduced the amount of CFU/mg to 94.13%. Conclusion: Using photodynamic therapy causes a reduction in the biofilm and inhibits the growth of the E. faecalis bacterium. In addition, in this study, MTAP with a concentration of 1 mg/mL was used, which expunged the bacteria completely. Meanwhile, calcium hydroxide had the weakest effect of all on the E. faecalis bacterium.